Paynter, Eleanor, Emergency in Transit: Witnessing Migration in the Colonial Present - Violetta Ravagnoli (European Journal of Life Writing, 2025)
In Emergency in Transit, Eleanor Paynter redefines contemporary Mediterranean migration, challenging dominant narratives, especially in Italy, that portray it as a sudden, unmanageable “crisis.” The book identifies the Italian government's response to migration as a problem of short-sightedness, since it approaches migration as an emergency situation. The weight of this critique comes from its focus on witness testimonies, a methodological commitment that is also a call to action. Paynter believes that changing the language around migration will change the dominant narrative that migration is a crisis. The book highlights how people held “in transit” respond to and resist this narrative and its government apparatus by analyzing the testimonies and cultural productions of migrants themselves. Drawing on oral histories, ethnography, and analysis of literature, film, and visual art published and set in Italy, Paynter contributes to critical refugee studies and postcolonial Italian studies, offering a call to reimagine mobility and belonging within the migrant experience. One of Paynter’s most compelling contributions is the use of migrants’ memoirs as witness literature, which challenges the erasures of official narratives and asserts migrants’ right to narrate their own histories.